Gender Differences and the Relationship of Motor, Cognitive and Academic Achievement in Omani Primary School-Aged Children - Zayed, Kashef; Jansen, Petra (Frontiers in Psychology, 2018)
Until now, there has been no integrated study of the cognitive, motor and academic developments in children in the Arab world. In this study we investigated gender differences in those three areas in primary school-aged children in Oman and as well as the inter-relations between those three aspects of development. Ninety-five third graders completed four working memory tests, a mental rotation test and a motor test. Furthermore, the marks in math, science and Arabic language were registered. The result showed that there were small gender differences: Girls performed better in one of the working memory tests and boys in the coordination motor test. The study also showed that there were significant correlations between cognitive variables and academic performance, as well as two significant correlations between motor performance and marks in math and science. Marks in math correlated with the performances in the 20 meters run and the coordination test, whereas the marks in science correlated with the ball-leg-wall test, the coordination test, and the endurance test. Regression analysis showed that all marks were predicted by the working memory and mental rotation performance as well as the motor ability. This means that academic achievement in Oman could be predicted by basic cognitive as well as motor abilities.